1. The problem statement, all variables and given/known data Using Hess's law, calculate the ΔH value for the following reaction: FeO(s)CO(g)→Fe(s)+CO2(g) Use these three reactions: 1. Fe2O3(s)+3CO(g)→2Fe3O4(s)+CO2(g) ΔH= -25.0 kJ 2. 3Fe2O3(s)+CO(g)→2Fe3O4(s)+CO2(g) ΔH= -47.0 kJ 3. Fe3O4(s)+CO(g)→3FeO(s)+CO2 ΔH= +38.0 kJ 2. Relevant equations 3. The attempt at a solution This is what I have done so far: Reversed reaction 3 3FeO(s)+CO2→Fe3O4(s)+CO(g) ΔH = -38.0 kJ I've tried some other things but each time I get the incorrect answer. The examples that I was shown were way easier than this. I'm not really sure what to do next. I reversed reaction 3 to get FeO on the left side. Any help on the steps I should take to complete this would be great... I find this question very confusing.